Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 33719 species occurrences available in GBIF matching the query: { "and" : [ "Country is Brazil", "HasGeospatialIssue is false", "Geometry POLYGON((-106.00 -45.32,-106.00 19.17,4.75 19.17,4.75 -45.32,-106.00 -45.32))", "Year 1850-1920" ] } The dataset includes 33719 records from 164 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0080630-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences